2007
DOI: 10.1002/cbdv.200790115
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Permeabilization of a Mammalian Neuroendocrine Cell Type (PC12) by the Channel‐Forming Peptides Zervamicin, Alamethicin, and Gramicidin

Abstract: Zervamicin IIB (ZER) is a 16-mer peptaibol that produces voltage-dependent conductances in artificial membranes, a property considered responsible for its antimicrobial activity to mainly Gram-positive microorganisms. In addition, ZER appears to inhibit the locomotor activity of the mouse (see elsewhere in this Issue), probably by affecting the brain. To examine whether the electrophysiological properties of the neuronal cells of the central neural system might be possibly influenced by the pore forming ZER, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Further increasing the amount of 1 applied to cells (10 μM) led to the rapid onset of linear leak currents, which agreed with results for the calcein leakage assay. Similar results were also observed in the MIA PaCa-2 cell line and are consistent with the known voltage dependence and pore-forming properties of the peptaibol alamethicin, which has long been used as a model compound for studying conductance through voltage-gated ion channels (56). Therefore, while 1 was clearly able to enter cells at cytotoxic concentrations without causing visible disruption to membranes in AFM and calcein release studies, the acute ion leakage initiated in patch-clamp studies, at its minimum cytotoxic concentration, suggested that 1 still retained a certain degree of plasma membrane-disrupting capacity, which likely contributed in part to its cytotoxic capabilities.…”
Section: Partial Hydrolysis Of Gichigamins Reveals Structural Requiresupporting
confidence: 87%
“…Further increasing the amount of 1 applied to cells (10 μM) led to the rapid onset of linear leak currents, which agreed with results for the calcein leakage assay. Similar results were also observed in the MIA PaCa-2 cell line and are consistent with the known voltage dependence and pore-forming properties of the peptaibol alamethicin, which has long been used as a model compound for studying conductance through voltage-gated ion channels (56). Therefore, while 1 was clearly able to enter cells at cytotoxic concentrations without causing visible disruption to membranes in AFM and calcein release studies, the acute ion leakage initiated in patch-clamp studies, at its minimum cytotoxic concentration, suggested that 1 still retained a certain degree of plasma membrane-disrupting capacity, which likely contributed in part to its cytotoxic capabilities.…”
Section: Partial Hydrolysis Of Gichigamins Reveals Structural Requiresupporting
confidence: 87%
“…Melittin, a cationic 2.6 kDa peptide from the Apis mellifera bee venom, is hemolytic and cytotoxic starting from ~0.5 µM (1.3 µg/mL), with maximum activity at ~7 and 20 µM (18 and 52 µg/mL), respectively [31,32]. The peptaibols alamethicin and zervamicin permeabilize plasma membrane of mammalian somatic cells at concentrations of ~5 µM (10 µg/mL) [33]. Other peptides display the membrane activity and toxicity at comparable or higher concentrations [34].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, undifferentiated PC12 cells were round cells with a halo and differentiated cells became the shape of sympathetic neurons and grew neurites. 55 By analyzing neurite outgrowth, it could be found that cells on all groups had neurite, and the cells cultured in NH 2 -MXene/PLLA under a rotating magnetic field possessed the longest neurite, indicating its excellent differentiation performance. 56 The percentage and neurite length of differentiated PC12 were determined from optical images.…”
Section: Cell Differentiationmentioning
confidence: 95%